High-Energy Charged Particles Their Chemistry and Use as Versatile Tools for Nanofabrication - Seki, Shu. (SpringerBriefs in Molecular Science,, 2015)
This book features comprehensive explanations from the classical theory of high-energy particle interactions with matter to their use for a novel nanofabrication technique for various organic soft materials. Potential readers include scientists and engineers in both academia and industry, as well as students of materials science, nanotechnology, and nuclear power engineering. Readers will learn about the historical research background of radiation chemistry and interactions of an accelerated particle with matter, and then move on to recent research topics having to do with nanofabrication of soft materials by using single charged particles with high energy. Target materials of the highlighted novel technique include proteins, thermo-responsive and photo-responsive polymers, semiconducting polymers, and even small organic molecules. The descriptions of these various newly developed nanomaterials will interest a broad spectrum of readers and provide them with a new perspective. The many conceptual illustrations and microscopic images of nanomaterials that are included will help readers to easily understand the contents of the book.